2013
DOI: 10.1088/0029-5515/53/2/023006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of oxygen impurity transport using the O4+visible spectral line in the Aditya tokamak

Abstract: Intense visible lines from Be-like oxygen impurity are routinely observed in the Aditya tokamak. The spatial profile of brightness of a Be-like oxygen spectral line (2p3p 3D3–2p3d 3F4) at 650.024 nm is used to investigate oxygen impurity transport in typical discharges of the Aditya tokamak. A 1.0 m multi-track spectrometer (Czerny–Turner) capable of simultaneous measurements from eight lines of sight is used to obtain the radial profile of brightness of O4+ spectral emission. The emissivity profile of O4+ spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…The radial emissivity profiles were obtained using an Abel-like matrix inversion technique [19] from the chord integrated brightness of O 4+ emissions. The details of this conversion have been described in the references [15,20]. The error estimation was done by incorporating the statistical error present in the absolute calibration and the one due to the spectral line fitting using a Gaussian profile to obtain the brightness, which is the area under the curve of the spectral line profile.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radial emissivity profiles were obtained using an Abel-like matrix inversion technique [19] from the chord integrated brightness of O 4+ emissions. The details of this conversion have been described in the references [15,20]. The error estimation was done by incorporating the statistical error present in the absolute calibration and the one due to the spectral line fitting using a Gaussian profile to obtain the brightness, which is the area under the curve of the spectral line profile.…”
Section: Methodsmentioning
confidence: 99%
“…This higher value of D compared to the calculated one by neo-classical transport theory is explained using the fluctuation induced transport. It was found that the transport driven by the ion temperature gradient (ITG) and dissipative trapped electron (DTE) modes was good enough to explain the diffusivity in the high field side, and the further higher value of diffusivity in the low field side was explained by using the combination of ITG and resistive ballooning modes (RB) [15]. The error bars in D represent the modification of the required diffusion coefficients to get the best-fit between experimental and calculated emissivity profiles due to the charge in the T e profile peaking factor.…”
Section: Modeling Of the O 4+ Emissivity Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The spatial profile of H α emission is regularly measured by a multi-track spectrometer. This diagnostic consists of a 1-m visible spectrometer having a grating with 1800 grooves/mm [17]. The detector, coupled on the focal plane of the exit port of the spectrometer, is a charge-coupled device (CCD) having a dimension of 1024 × 256 pixels and each pixel size is 26 × 26 µm 2 .…”
Section: Aditya Tokamak and Its Diagnosticsmentioning
confidence: 99%
“…Therefore, the transport of fuel and impurities is largely affected by the magnetic field structure. In tokamaks, edge impurity and hydrogen emissions have been investigated using spectroscopic systems, [2][3][4][5] where interesting plasma transport properties have been revealed. Helical devices, however, usually have a complex magnetic field structure due to the intrinsic non-axisymmetric configuration as compared to tokamaks, and we need special care to conduct the spectroscopic measurements.…”
Section: Introductionmentioning
confidence: 99%